Anti-inflammatory effect of limonin from cyclodextrin (un)processed orange juices in in vivo acute inflammation and chronic rheumatoid arthritis models. (October 2018) - Vieira da Silva, Susana A.; Clemente, Ana; Rocha, João; Direito, Rosa; Marques, Helena Cabral; Sepodes, Bruno; Figueira, Maria-Eduardo; Ribeiro, Maria H.
Graphical abstract: Highlights: Limonin was successfully complexed in β - and γ -cyclodextrins. Limonin (in orange juice) complexation of 92.5% and 82% was obtained with β - and γ -cyclodextrins. Limonin showed a high anti-inflammatory effect in acute and chronic inflammation in vivo models. Limonin, in orange juice, complexed with β -cyclodextrins led to reduction of edema. Bitter taste of orange juice was suppressed (limonin) with the maintenance of healthy properties. Abstract: Citrus fruits and juices are recognized as one of the most healthful components of the human diet. Limonin is a bitter compound, highly oxygenated triterpenoid, that occurs as aglycones in some citrus fruits. The aim of this work was to (i) complex limonin in cyclodextrins to reduce bitterness in orange juice and (ii) evaluate limonin anti-inflammatory activity, in standard solutions and orange juice, in in vivo acute and chronic models. Two local in vivo inflammation models were used (i) an acute (carrageenan-induced paw edema) and (ii) a chronic (collagen-induced arthritis). In both models, the results showed a significant reduction of the volume of the edema. The radiographic examination of the hind paws confirmed that administration of limonin was able to reduce the degree of bone resorption, soft tissue swelling and osteophyte formation, improving articular function in treated animals. These results are very promising for the implementation of a bitter taste reduction of limonin in citrus juices by complexation in cyclodextrins with the maintenance of anti-inflammatory activity and may open new applications in food area.